Ukrainian roots of Professor Volodymyr Sokovich, as the basis of his scientific and social outlook - Fesovets, O. R. (History of science and technology, 2018)
The article gives an overview of the origin of the family, the childhood, the acquisition of secondary education and the start of education at the higher school of the outstanding Ukrainian railway scientist, the founder of the scientific school "Organization of Railway Transportation" Volodymyr Sokovich. The biography of his father, Olexandr Sokovich (1840-1886), a well-known Ukrainian teacher, teacher of mathematics, physics and geography, author of a number of textbooks and teaching aids on these subjects, the head of several real colleges and the Belotserkovsky Gymnasium is highlighted. Particular mention is made of membership of O. Sokovich in the South-Western Division of the Russian Geographical Society, which became the center of the scientific and socio-cultural life of Kiyv and Ukraine of its time. It was also determined that his elder brother Evgen Sokovich (1864 - 1946) played a decisive role in the choice of the future scientist for the railway worker. which later, in the period of existence of the Ukrainian People’s Republic, became Minister of Railways of its government. A number of facts of his activity are highlighted in this post. The period of training of Volodymyr Sokovich in the Second Kyiv Gymnasium is analyzed, the natural inclination of the schoolboy to exact sciences is noted - especially to mathematics. In connection with which, he began to receive higher education at the Physics and Mathematics Faculty of Kyiv University of St. Volodymyr, and only then entered the St. Petersburg Institute of Railway Engineers. Summarizing the work, we can state that the article identifies the reasons that gave the impetus for the formation of an outstanding scientific personality of the Doctor of Technical Sciences, Professor Volodymyr Sokovich.